EMERGING ADULTHOOD, IDENTITY STATUS AND PARENTAL CONTROL - Beričić, Ardijana; Erceg, Inja (Primenjena psihologija, 2019)
The aim of this study was to examine the differences between groups of individuals of different student status in characteristics of emerging adulthood and identity status, and to examine the correlation between parental control and identity dimensions of emerging adults. The study included 363 participants aged from 18 to 25 years. The following measures were used in the study: The IDEA: Inventory of the Dimensions of Emerging Adulthood, Ego Identity Process Questionnaire, scales of parental psychological control, behavioral control and helicopter behaviors, and subjective sense of adulthood was measured with one item. Results show that individuals of different student status statistically differ in three dimensions of emerging adulthood: the age of possibilities, the age of instability and the age of feeling in-between, and the supplementary scale of the age of focus on others. Students, more than graduates, feel that for them emerging adulthood is the age of instability and the age of feeling in-between, while non-students, more than students, feel that emerging adulthood is the age of focus on others. Most individuals who graduated considered themselves as adults, while non-students and students mostly state that they consider themselves adults only in certain aspects. There were no differences in the identity status between groups of different student status. The commitment dimension is significantly negatively related to mother’s behavioral and psychological control and to father’s psychological control. The exploration dimension is only significantly negatively related to mother’s helicopter behavior.